1999
DOI: 10.1002/(sici)1097-4660(199904)74:4<322::aid-jctb35>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

On the kinetics of magnesia hydration in magnesium acetate solutions

Abstract: : High-quality magnesium hydroxide powders can be produced by hydrating slow-reacting magnesia in dilute magnesium acetate solutions. The kinetics of this process are very crucial for process design and control, and for the production of a powder with desirable particle morphology. In this work, industrial heavily-burned magnesia powders were hydrated in 0.01-0.1 mol dm-3 magnesium acetate solutions at temperatures ranging between 333 and 363 K. Examination of the magnesium hydroxide produced and the analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
91
0
8

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(105 citation statements)
references
References 7 publications
6
91
0
8
Order By: Relevance
“…Many studies have been carried out to understand the hydration mechanisms of magnesia [6][7][8][9][10] in order to develop anti-hydration techniques. [11][12][13][14][15] Nevertheless, the results attained are quite diverse due to differences in the magnesia source, purity, temperature, hydration time and the chemical environment where the hydration is performed.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been carried out to understand the hydration mechanisms of magnesia [6][7][8][9][10] in order to develop anti-hydration techniques. [11][12][13][14][15] Nevertheless, the results attained are quite diverse due to differences in the magnesia source, purity, temperature, hydration time and the chemical environment where the hydration is performed.…”
Section: Introductionmentioning
confidence: 99%
“…In the experiment conducted in the present study, the hydration process of MgO occurs at a pH value of 10±0.5 and can be significantly decreased in a strong basic pH region due to a low degree of solubility of MgO [19]. It should also be mentioned here that an extremely rapid hydration rate of magnesia will result in the formation of relatively larger magnesium hydroxide aggregates, which comprise submicroscopic crystallites of a wider surface area-a particle morphology that is not acceptable for some applications [20].…”
Section: Causticization-hydration Process Of the Intermediate Flotatimentioning
confidence: 99%
“…Assuming that s , r o , M s , k, and C Bg remain constant at a given temperature, Eq. [8] can be rewritten as [9] where k r is a new constant. The term (1 Ϫ (1 Ϫ X) 1/3 ) should be a linear function of time if the reduction is controlled by the chemical reaction at the interface between the product…”
Section: Chemical Reaction As the Rate-controlling Stepmentioning
confidence: 99%
“…To encounter the particles with a range of size distributions, Filippou et al [8] have suggested an elegant way of processing the experimental data. The powder bed can be assumed to contain particles of a number of small size ranges.…”
Section: Chemical Reaction As the Rate-controlling Stepmentioning
confidence: 99%